Systematic Literatur Review dan Bibliometrik Penerapan Life Cycle Assessment pada Produk Daur Ulang Pengelolaan Sampah Berkelanjutan - Prastiti Ari Untari; Devi Maulida Rahmah; Koko Iwan Agus Kurniawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The growing global population has led to a surge in waste, which is having an increasing impact on environmental sustainability. One alternative to address this issue is waste recycling. The recycling process involves energy consumption and the use of chemicals, which can potentially result in environmental impacts. This study aims to provide a comprehensive understanding of the application of Life Cycle Assessment (LCA) to measure the environmental impacts of recycled products. It examines research trends and directions through a Systematic Literature Review (SLR) combined with bibliometric analysis using the ScienceDirect database for the period 2021–2026. The literature review focuses on recycled products within the scope of LCA systems and environmental impact methods in Life Cycle Impact Assessment (LCIA). The results of this study indicate that the application of LCA for recycled products is predominantly conducted in the plastic and battery industries. However, further application of LCA to recycled products across all industrial sectors promotes green industry policies and sustainability.